THE ROLE OF THE POLICE IN OVERCOMING THE CRIME OF BEGAL IN THE MEDAN CITY AREA - Micael Jeriko Damanik; Parlindungan Purba; Venni Monika Saragih (Journal of International Islamic Law, Human Right and Public Policy, 2023)
In this in-depth study, the creator hopes to understand the criminal sanctions for perpetrators of the wrongful act of Robbery with Brutality (BEGAL), the elements that cause the wrongful act of robbery with brutality, and the duties of the police regarding criminal demonstrations of robbery with brutality. in Medan City and the police. In this examination the author used a strategy of examining the information used which was recorded in hard copy form as a result of this exploration, especially subjective examination. Subjective examination means highlighting more valid and clear investigations and this subjective exploration strategy is also expected to illustrate the examination of information in a narrative manner. Robbery with barbarity (BEGAL) or the danger of brutality is an act of lawlessness that disturbs society. Robbery as a traditional wrongdoing has really turned into a criminal specialty that still disturbs Indonesian culture where this wrongful act of robbery is carried out in the city by seizing or taking motorized vehicles, usually the perpetrators complete their activities by using firearms, weapons. sharp and so on. where executions usually took place in distant streets.